Screening for Risk of Developmental Delay in a primary care setting using the Nippising District Developmental Screen. (1st June 2016) - Zabih, W; Parkin, P; Borkhoff, C; Heuvel, M Van den; Korosheygi, C; Maguire, J; Birken, C; Cairney, J; ,
Abstract: BACKGROUND: Early growth and development in the first five years of life is strongly associated with health outcomes. The Nipissing District Developmental Screen (NDDS) is a free parent-reported screening tool recommended by the Canadian Pediatric Society as one of the tools for developmental screening in children OBJECTIVES: To determine the prevalence of a positive screen for risk of developmental delay in a cohort of healthy children at 18-months and 5 years. To identify risk factors (child, socio-demo-graphic and home environment) associated with a positive screen for risk of developmental delay. DESIGN/METHODS: A cross-sectional study of healthy Canadian children attending 18-months and 5 year well-child visits between June 2008 and February 2015 was conducted through the TARGet Kids! practice-based research network. Multivariable logistic regression was used to identify risk factors associated with a positive screen for developmental delay. Risk factors of development delay identified from literature were:, male sex, low birth weight, low income, low maternal education, maternal unemployment, non-industrialized immigrant status, single parent family, only child and older maternal age. RESULTS: 1086 children (53% male) at 18 months and 575 children (51% male) at 5 years were included in the final analysis. At 18 months, 341 (31.4%) of children (95% CI, 28.7% - 34.3%) and at 5 years 166 (28.9%) (95% CI, 25.2% -32.8%) were screen positive base on 1+ flag NDDS. At 18 months, children with a low birthweight (OR=1.66; 95% CI 1.22-2.28), with a mother with low education (OR=1.75; 95% CI 1.07-2.85), and those from non-industrialized immigrant families (OR=1.85; 95% CI 1.37-2.49) were associated with an increased odds of a positive screen for developmental delay based on the 1+ NDDS flag. A female child (OR=0.74; 95% CI 0.57-0.96) and an only child (OR=0.76; 95% CI 0.57-0.99) were associated with a decreased odds of a positive screen for developmental delay. At 5 years, factors associated with a positive screen for developmental delay based on the 1+ NDDS flag were: low maternal education (OR 2.24; 95% CI 1.14-4.39) (children had 2.24 times greater odds of a positive screen for developmental delay) and older maternal age (OR 1.05; 95% CI 1.00-1.09) (every 1-year increase in maternal age, children had 1.05 times greater odds of a positive screen for developmental delay). A female child was associated with a decreased odds of a positive screen for developmental delay (OR=0.66; 95% CI 0.46-0.96) based on the 1+ NDDS flag. CONCLUSION: In a population of healthy urban children the NDDS identified 30% at both 18 month and 5 years at risk for developmental delay. Risk factors for developmental delay were associated with a positive NDDS screen.